1984
DOI: 10.1017/s0140525x00018938
|View full text |Cite
|
Sign up to set email alerts
|

Sensation seeking: A comparative approach to a human trait

Abstract: A comparative method of studying the biological bases of personality compares human trait dimensions with likely animal models in terms of genetic determination and common biological correlates. The approach is applied to the trait of sensation seeking, which is defined on the human level by a questionnaire, reports of experience, and observations of behavior, and on the animal level by general activity, behavior in novel situations, and certain types of naturalistic behavior in animal colonies. Moderately hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
232
0
18

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(259 citation statements)
references
References 245 publications
(182 reference statements)
9
232
0
18
Order By: Relevance
“…Sensation seeking-The Sensation Seeking Scale, Form V (SSS-V; Zuckerman, 1984) is a 40-item questionnaire that was used to measure maternal levels of stimulation and arousal. The SSS-V consists of four subscales: thrill and adventure seeking (desire to partake in activities involving physical danger), experience seeking (desire to seek new experiences through mind and senses), disinhibition (need to disinhibit behavior in the social sphere), and boredom susceptibility (aversion to repetitive experience of any kind).…”
Section: Methodsmentioning
confidence: 99%
“…Sensation seeking-The Sensation Seeking Scale, Form V (SSS-V; Zuckerman, 1984) is a 40-item questionnaire that was used to measure maternal levels of stimulation and arousal. The SSS-V consists of four subscales: thrill and adventure seeking (desire to partake in activities involving physical danger), experience seeking (desire to seek new experiences through mind and senses), disinhibition (need to disinhibit behavior in the social sphere), and boredom susceptibility (aversion to repetitive experience of any kind).…”
Section: Methodsmentioning
confidence: 99%
“…The biological basis of sensation seeking, which has received considerable research attention (see Zuckerman, 1984), provides further insight into the prevalence of reckless behavior during adolescence. Table 1 summarizes the evidence connecting biological factors to sensation seeking and reckless behavior.…”
Section: Sensation Seekingmentioning
confidence: 99%
“…Scores on the SSS have been found to be related to Average Evoked Potential (AEP) augmenting-reducing, which is a measure of the brain's tendency to respond to a strong visual or auditory stimulus by augmenting the stimulus (increasing its intensity) or reducing it (responding less to a highly intense stimulus than to a slightly less intense stimulus). Augmenting is considered to indicate a "strong" nervous system, while reducing represents a "weak" one (Zuckerman, 1984). A number of studies (Buchsbaum, 1971;Coursey, Buchsbaum, & Frankel, 1975;Lukas & Siegel, 1981) have shown SSS scores to be positively related to augmenting, especially the Disinhibition subscale, and it has also been shown that younger subjects tend to be augmenters, while older subjects tend to be reducers (Buchsbaum, 1974).…”
Section: Sensation Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…In several of the concepts of temperament (see Strelau, 2001;Strelau & Angleitner, 1991, 1994Zuckerman, 1979Zuckerman, , 1984Zuckerman, , 1994, it is emphasized that temperament traits determine an individual's need for stimulation and are responsible for regulating stimulation. Studies have shown that individuals who have a high need for stimulation prefer highly stimulative actions and situations, while those with a low need for stimulation prefer actions and situations of low stimulative value (Strelau, 2001;Strelau & Zawadzki, 1998;Zuckerman, 1979Zuckerman, , 1984Zuckerman, , 1994. Studies on the relationship of temperament traits (linked with the need for stimulation) and musical preferences show similar relationships.…”
Section: Introductionmentioning
confidence: 99%